Two‐drug vs. three‐drug combinations for HIV‐1: Do we have enough data to make the switch?. (1st March 2019) - Moreno, S; Perno, CF; Mallon, PW; Behrens, G; Corbeau, P; Routy, J‐P; Darcis, G
Abstract : Three‐drug combination antiretroviral therapy (ART) became available in 1996, dramatically improving the prognosis of people living with HIV. The clinical benefits of ART are due to the sustained viral load suppression and CD4 T cell gains. Major drawbacks of the first ART regimens were adverse events, and high pill burden, which led to the reduction of drug adherence resulting in frequent treatment discontinuations and the development of drug resistance. Due to increased viral potency of new antiretroviral drugs consideration of a two‐drug combination therapy repositioning occurred in an effort to reduce adverse events, drug‐drug interactions and cost, while maintaining a sustained antiviral effect. Various combinations of two‐drug regimens have been studied, and non‐inferiority compared to a three‐drug regimen has been shown only for some of them. In addition, a two‐drug combination regimen may not be suitable for every patient, especially those who are pregnant, those with tuberculosis or coexisting HBV infection. Furthermore no information has been generated concerning the secondary transmission of HIV from patients who have undetectable plasma viral load on two‐drug regimens. Additional studies of two‐drug combinations are also necessary to evaluate the debated existence of low viral replication in tissues and on immune activation. While there is no urgent need to routinely switch patients to two‐drug combination therapy, due to the availability of drug combinations without significant toxicities, dual regimens represent a suitable option that deserve long‐term evaluation before being introduced to clinical practice.